The Effect of Digital Financial Literacy and Economic Stress on Household Financial Management Quality with Self-Control as a Mediating Variable - U. Uus Ustadzi; Ahmad Soleh (Universitas 17 Agustus 1945 Semarang, 2026)
This study aims to analyze the effect of digital financial literacy and economic stress on household financial management quality, with self-control as an intervening variable. This research adopts a quantitative approach using Partial Least Square–Structural Equation Modeling (PLS-SEM). Data were collected through questionnaires distributed to household respondents and analyzed using SmartPLS. The results indicate that digital financial literacy has a positive and significant effect on household financial management quality and self-control. In contrast, economic stress does not have a significant effect on either self-control or household financial management quality. Furthermore, self-control does not mediate the relationship between digital financial literacy and economic stress on household financial management quality. These findings highlight the importance of enhancing digital financial literacy to improve household financial management in the digital era.